Efficacy of short-term high-dose statin in preventing contrast-induced nephropathy: a meta-analysis of seven randomized controlled trials. - Yongchuan Li (Public Library of Science (PLoS), 2012)
Background A few studies focused on statin therapy as specific prophylactic measures of contrast-induced nephropathy have been published with conflicting results. In this meta-analysis of randomized controlled trials, we aimed to assess the effectiveness of short-term high-dose statin treatment for the prevention of CIN and clinical outcomes and re-evaluate of the potential benefits of statin therapy. Methods We searched PubMed, OVID, EMBASE, Web of science and the Cochrane Central Register of Controlled Trials databases for randomized controlled trials comparing short-term high-dose statin treatment versus low-dose statin treatment or placebo for preventing CIN. Our outcome measures were the risk of CIN within 2-5 days after contrast administration and need for dialysis. Results Seven randomized controlled trials with a total of 1,399 patients were identified and analyzed. The overall results based on fixed-effect model showed that the use of short-term high-dose statin treatment was associated with a significant reduction in risk of CIN (RR =0.51, 95% CI 0.34-0.76, p =0.001; I(2) = 0%). The incidence of acute renal failure requiring dialysis was not significant different after the use of statin (RR = 0.33, 95% CI 0.05-2.10, p = 0.24; I(2) = 0%). The use of statin was not associated with a significant decrease in the plasma C-reactive protein level (SMD -0.64, 95% CI: -1.57 to 0.29, P = 0.18, I(2) = 97%). Conclusions Although this meta-analysis supports the use of statin to reduce the incidence of CIN, it must be considered in the context of variable patient demographics. Only a limited recommendation can be made in favour of the use of statin based on current data. Considering the limitations of included studies, a large, well designed trial that incorporates the evaluation of clinically relevant outcomes in participants with different underlying risks of CIN is required to more adequately assess the role for statin in CIN prevention.